Milton Friedman and the Emergence of the Permanent Income Hypothesis - Hsiang-Ke Chao (Tinbergen Institute, 2001)
The purpose of this paper is to investigate the evolution of MiltonFriedman's permanent income hypothesis from the 1940s to 1960s, andhow it became the paradigm of modern consumption theory. Modellingunobservables, such as permanent income and permanent consumption, isa long-standing issue in economics and econometrics. While theconventional approach has been to set an empirical model to makepermanent income measurable, the historical change in the meaningof that theoretical construct is also of methodological interest.This paper will show that the concepts of unobservables, especiallypermanent income, in Friedman's work was fluid and depended on theinstruments used.
Keywords: 330; Einkommenshypothese; Konsumtheorie; Kritik; Theorie